THE EFFECT OF PERCEIVED BENEFITS, PERCEIVED RISK, AND PERCEIVED SECURITY ON THE INTENTION TO USE DANA AS THE E-MONEY APPLICATION AMONG STUDENTS OF SAM RATULANGI UNIVERSITY - Sasiang, Bryan Jonathan Kevin; Kindangen, Paulus; Rogi, Mira H (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study investigates the impact of perceived benefits, perceived risk, and perceived security on students' intention to use DANA, an e-money application, among students of Sam Ratulangi University. With the increasing shift towards digital transactions, it is essential to understand the factors influencing the adoption of e-money services. Using a quantitative method, data was collected from 100 students via an online survey. The results indicated that perceived benefits and perceived security positively affect the intention to use DANA, while perceived risk negatively affects it. These findings provide insights for service providers to improve their offerings and address user concerns, particularly regarding security   Keyword: Perceived Benefits, Perceived Risk, Perceived Security, E-Money, Intention To Use